Conformal deposition of atomic TiO2 layer on chalcogenide nanorod with excellent activity and durability towards solar H2 generation - Liu, Maochang; Xue, Fei; Wang, Xixi; Fu, Wenlong; Wang, Yi; Lu, Youjun; Li, Naixu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •Ultrathin TiO2 shell was coated on chalcogenide nanorod as a protecting layer.•The synthesis relies on kinetic control for layer-by-layer deposition of TiO2.•The heterostructure enables superior activity and stability of solar H2 evolution.•Charge transfer is controlled by type-II band alignment and tunneling effect. It has been a subject of intensive research on avoiding photocorrosion of sulfide photocatalysts while retaining their activity for visible-light-driven photocatalysis. Herein, using Cd0.9Zn0.1S (CZS) nanorod as an example, we report an effective strategy based upon conformal coating of an ultrathin pinhole-free TiO2 shell, with controllable thickness from 2 to 7 nm, on the nanorod as protecting layer. The synthesis relies on the use of a syringe pump for kinetic control, by which, TiO2 can grow on the surface of CZS in a layer-by-layer mode. The core–shell heterostructures were found with excellent photocatalytic performance toward solar hydrogen production from a Na2S-Na2SO3 aqueous solution. The reaction can stably proceed for 200 h without notable decay of the hydrogen evolution rate. A volcano-type relationship between the mass activity and the shell thickness was gained either in the presence of a cocatalyst or not. The heterostructure with a shell thickness of 2 nm presented the highest H2-evolution activity with a quantum efficiency of 19%. However, the one with a shell thickness of 7 nm, instead, was found to be more active, with a quantum efficiency reaching 44%, when 1 wt% NiSx cocatalyst was introduced. It is believed that photogenerated electrons transfer from CZS to TiO2, while the holes vanish via quantum-tunneling-induced recombination with the electrons. This work suggests that sulfide photocatalysts with desirable efficiency and corrosion resistance could be achieved by introducing conformal atomic TiO2 layers.